The Effect Of Cholecalciferol On Fasting Blood Glucose In Streptozotocin-induced Hyperglycemia Mice - Elly Nurus Sakinah (UPT Penerbitan Universitas Jember, 2014)
Glucose uptake into skeletal muscle cells require insulin-dependent and insulin independent signaling pathways, both leading to the translocation of glucose transporter-4 (GLUT4) to the plasma membrane. Insulin resistance occurs due to failure of insulin signaling to translocate GLUT4 resulting in the failure of glucose uptake and causing hyperglycemia. Cholecalciferol is known to have a function in regulating calcium homeostasis was shown to increase the synthesis of insulin and increasing insulin sensitivity. The purpose of this study is to explain the role of cholecalciferol to decreased fasting blood glucose in streptozotocin-induced hyperglyemia mice. 30 mice adapted for one week and then induced using 150mg/kgBW streptozotocin (STZ) intraperitoneally, After experiencing hyperglycemia mice were divided into 5 groups (n=6 each), Group I (hyperglycemic control), group II (25ng cholecalciferol), group III (50ng cholecalciferol), group IV (100ng cholecalciferol), and group V (metformin 300mg/kgBBB). Cholecalciferol given orally for 14th days. On day 15th the examination of fasting blood sugar levels were taken and the mice. Fasting blood sugar levels measured using a glucometer. Based on statistical analysis showed that there were significant differences in fasting blood sugar levels between treatment groups (p<0,001). Based on univariate regression analyses there was negative correlation of cholecalciferol with fasting blood glucose (p<0,001). Cholecalciferol may lower fasting blood sugar levels in hyperglycemia mice models. Keywords: cholecalciferol, fasting blood glucose, STZ.